Business structure analysis and internationalisation strategy development for Kontrax JSC, Bulgaria - Upponi, Priyanka; Jordanov, Nikolay; Ikhe, Pravin (2011)
The dark clouds of recession have spared none and Bulgaria is no exception to that. Kontrax, which relied heavily on public sector projects for its ICT solutions and System Integration business, is experiencing significant loss of revenue and drop in margins given the current economic scenario.